Sample deposition onto cryo‐EM grids: from sprays to jets and back. Issue 4 (7th April 2020) - Klebl, David P.; Monteiro, Diana C. F.; Kontziampasis, Dimitrios; Kopf, Florian; Sobott, Frank; White, Howard D.; Trebbin, Martin; Muench, Stephen P.
Abstract : Sample preparation within single‐particle cryo‐electron microscopy can still be a significant bottleneck, with issues in reproducibility, ice quality and sample loss. New approaches have recently been reported that use spraying or pin printing instead of the traditional blotting approach. Here, experience in the use of different nozzle designs and spraying regimes is reported together with their influence on the resulting spray and grid quality. Abstract : Despite the great strides made in the field of single‐particle cryogenic electron microscopy (cryo‐EM) in microscope design, direct electron detectors and new processing suites, the area of sample preparation is still far from ideal. Traditionally, sample preparation involves blotting, which has been used to achieve high resolution, particularly for well behaved samples such as apoferritin. However, this approach is flawed since the blotting process can have adverse effects on some proteins and protein complexes, and the long blot time increases exposure to the damaging air–water interface. To overcome these problems, new blotless approaches have been designed for the direct deposition of the sample on the grid. Here, different methods of producing droplets for sample deposition are compared. Using gas dynamic virtual nozzles, small and high‐velocity droplets were deposited on cryo‐EM grids, which spread sufficiently for high‐resolution cryo‐EM imaging. For those wishing to pursue a similar approach, an overview is given of the current use of spray technology for cryo‐EM grid preparation and areas for enhancement are pointed out. It is further shown how the broad aspects of sprayer design and operation conditions can be utilized to improve grid quality reproducibly.